Development of a Window-mounted Insulation Module using Blind Technology to Improve Comfort and Convenience - Lee, Heangwoo; Choi, Chang-ho; Kim, Suktae (International Journal of Engineering and Technology, 2019)
The increase in the amount of energy consumed by buildings has led to a growing number of studies that attempt to solve this problem. One approach that has been proposed in some studies is the use of air caps, a type of material that can be attached to the exterior surface of a building to improve its insulation performance and thus save energy. However, air caps are currently difficult to attach, and there has been a problem of deteriorating views caused by the attachment method, which applies the air caps to the front surface of windows. Therefore, the objective of this study is to develop blind-type window-attaching-type air cap modules and use a full-scale test-bed to verify the energy saving effects on lighting devices and air-conditioning appliances. The conclusion reached is as follows: 1) The blind-type window-attaching-type air cap module suggested in this study is designed to open and close the blind with its air cap attached to the wing plate of the blind in order to easily shift the status of air cap application and minimize the extent to which it interferes with the view. 2) The window to which the air cap is attached, compared to unattached ones, has a 3.9–12.8% increase in energy consumption for lighting, which makes it inappropriate for lighting energy saving. 3) The blind-type window-attaching-type air cap module, compared to the current air cap-related technology, is capable of achieving a 4.3–7.4% reduction in the energy used for air-conditioning. 4) The blind-type window-attaching-type air cap module, compared to current air cap technology, is capable of achieving a 3.7–1.3% reduction in the energy used for air conditioning and lighting, and is thus useful for saving building energy.